English: English - Herlambang Eka Persada; Khusnul Bayu Aji (ASEAN Journal on Hospitality and Tourism, 2021)
The purpose of this study is to examine how social capital affected the resilience strategy in a tourist destination during the COVID-19 pandemic by visiting Nglanggeran Tourism Village case. Nglanggeran has become one of  tourist destinations in DIY, or even in Indonesia, that was formally reoperated earliest whilst a pandemic is still underway. On the other hand, they are regarded as one of the best tourism villages in Indonesia and South-East Asia that are entirely run by locals, with many representatives from other tourism villages frequently visiting Nglanggeran for benchmarking purposes. This is a descriptive study that employs a qualitative research approach. The data for this study was compiled through observation and semi-structured interviews to obtain primary data, while secondary data was collected through literature reviews related to the scope and focus of the study. The findings of the study show that, in the context of Nglanggeran’s tourism management at the time of the crisis induced by the COVID-19 pandemic, social capital influenced resilience strategy, which would have been closely associated with: a) practicing new norms in the making; b) consolidating trust; and c) bridging partnerships among stakeholders.